Health ethics and Indigenous ethnocide. (20th June 2019) - Matthews, Richard
Abstract: In colonial societies such as Canada the implications of colonialism and ethnocide (or cultural genocide) for ethical decision‐making are ill‐understood yet have profound implications in health ethics and other spheres. They combine to shape racism in health care in ways, sometimes obvious, more often subtle, that are inadequately understood and often wholly unnoticed. Along with overt experiences of interpersonal racism, Indigenous people with health care needs are confronted by systemic racism in the shaping of institutional structures, hospital policies and in resource allocation decisions. Above all, racism is a function of state law – of the unilateral imposition of the settler society law on Indigenous communities. Indeed, the laws, including health laws, are social determinants of the ill‐health of Indigenous peoples. This article describes the problem of Indigenous ethnocide and explores its ethical implications. It thereby problematizes the role of law in health ethics.